Patterns of human–coyote conflicts in the Denver Metropolitan Area1. Issue 2 (23rd August 2012) - Poessel, Sharon A.; Breck, Stewart W.; Teel, Tara L.; Shwiff, Stephanie; Crooks, Kevin R.; Angeloni, Lisa
Abstract In many cities throughout North America, human–coyote conflicts are an emerging problem. Little research has described temporal and spatial patterns of human–coyote conflicts, although such information can be an important step in developing and optimizing management efforts. We used reports from 22 entities within the Denver Metropolitan Area (DMA) in Colorado that provided information on coyote observations (signs, sightings, and encounters) and conflicts (incidents, pet‐attacks, and human‐attacks). Our objectives were to 1) define, quantify, and map categories of coyote observations and conflicts, and 2) investigate temporal and spatial patterns of conflicts, particularly related to land cover types and housing density classes. We compiled 4, 006 coyote reports, including 78 signs (1.9%), 3, 023 sightings (75.5%), 395 encounters (9.9%), 26 incidents (0.6%), 471 pet‐attacks (11.8%), and 13 human‐attacks (0.3%). We found a strong seasonal pattern with reports of both observations and conflicts highest during December–March and lowest during July–September. Numbers of coyote conflicts were disproportionately greater in open space and development land cover types (in contrast to natural and agricultural land cover) and in suburban housing areas (in contrast to urban, exurban, and rural areas). Hotspots of coyote conflicts were apparent in the southern region of the DMA, possibly because coyotes had better access to development, and hence interaction with residents, via natural areas bordering urban areas; reporting bias may have also influenced this outcome. Our results will help target management efforts, particularly those focused on people (e.g., education), but also highlight the critical need for improved methods of collecting conflict information via a standardized reporting mechanism to help reduce bias. © 2012 The Wildlife Society.